Variation in osteocytes morphology vs bone type in turtle shell and their exceptional preservation from the Jurassic to the present (2012)
Here we describe variations in osteocytes derived from each of the three bone layers that comprise the turtle shell. We examine osteocytes in bone from four extant turtle species to form a morphological ‘baseline’, and then compare these with morphologies of osteocytes preserved in Cenozoic and Mesozoic fossils. Two different morphotypes of osteocytes are recognized: flattened-oblate osteocytes (FO osteocytes), which are particularly abundant in the internal cortex and lamellae of secondary osteons in cancellous bone, and stellate osteocytes (SO osteocytes), principally present in the interstitial lamellae between secondary osteons and external cortex. We show that the morphology of osteocytes in each of the three bone layers is conserved through ontogeny. We also demonstrate that these morphological variations are phylogenetically independent, as well as independent of the bone origin (intramembranous or endochondral). Preservation of microstructures consistent with osteocytes in the morphology in Cenozoic and Mesozoic fossil turtle bones appears to be common, and occurs in diverse diagenetic environments including marine, freshwater, and terrestrial deposits. These data have potential to illuminate aspects of turtle biology and evolution previously unapproachable, such as estimates of genome size of extinct species, differences in metabolic rates among different bones from a single individual, and potential function of osteocytes as capsules for preservation of ancient biomolecules.